(a-2b)÷(a+2b)=4 [3(a-2b)÷4(a+2b)]+[3(a+2b)÷(a-2b)]最好能稍微讲讲为啥当(a-2b)÷(a+2b)=4时,求 [3(a-2b)÷4(a+2b)]+[3(a+2b)÷(a-2b)]的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 08:05:42
(a-2b)÷(a+2b)=4[3(a-2b)÷4(a+2b)]+[3(a+2b)÷(a-2b)]最好能稍微讲讲为啥当(a-2b)÷(a+2b)=4时,求[3(a-2b)÷4(a+2b)]+[3(a+
(a-2b)÷(a+2b)=4 [3(a-2b)÷4(a+2b)]+[3(a+2b)÷(a-2b)]最好能稍微讲讲为啥当(a-2b)÷(a+2b)=4时,求 [3(a-2b)÷4(a+2b)]+[3(a+2b)÷(a-2b)]的值
(a-2b)÷(a+2b)=4 [3(a-2b)÷4(a+2b)]+[3(a+2b)÷(a-2b)]
最好能稍微讲讲为啥
当(a-2b)÷(a+2b)=4时,求 [3(a-2b)÷4(a+2b)]+[3(a+2b)÷(a-2b)]的值
(a-2b)÷(a+2b)=4 [3(a-2b)÷4(a+2b)]+[3(a+2b)÷(a-2b)]最好能稍微讲讲为啥当(a-2b)÷(a+2b)=4时,求 [3(a-2b)÷4(a+2b)]+[3(a+2b)÷(a-2b)]的值
[3(a-2b)÷4(a+2b)]+[3(a+2b)÷(a-2b)]
=3÷4[(a-2b)÷(a+2b)]+3[(a+2b)÷(a-2b)]
因为(a-2b)÷(a+2b)=4 即 (a+2b)÷(a-2b)=1/4
所以3÷4[(a-2b)÷(a+2b)]+3[(a+2b)÷(a-2b)]
=3÷4×4+3×1/4=15/4
(a-b)^6*[-4(b-a)^3]*(b-a)^2÷(a-b)=求过程
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/b]
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/a]
4(a-b)3•(a+b)2÷【2(a+b)(a-b)】2
化简a/b(a-b)-b/a(a-b)其中a=3 b=-2
2(a+b)-[4(a+b)-3(a+b)]一[5(a-b)+(a-b)]过程
【(a+b)³-2(a+b)²-4(a+b)】÷(a+b)=?
(3/4)(a+b)(a-b)=2(a-b),题目条件是a,b不等,
(a-b)^2*(b-a)^5+(b-a)^3*(a-b)^4=?
(a^2+1)(-4a^2+1)+a^4-1 3a(a-b)(a+b)-6(b-a)^2a^2-9(a-b)^2= 3a(a-b)(a+b)-6(b-a)^2=
计算(a-b)^m(a-b)[2(b-a)]^3[(b-a)^5]^2÷(a-b)^m=
(a-2b)(3a+4b)+(2a-4b)(2a-3b)=(a-2b)*(
若a-b=4,3a+2b=6,3a(a-b)+2b(a-b)=( ).
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)
(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)
先化简,再求值:[(3a+2b)(3a-2b)-(a+2b)(5a-2b)]÷4a,其中a=2,b=-3
先化简再求值[(3a+2b)(3a-2b)-(a+2b)(a-2b)]÷(4a),其中|a-2|+(b+3)^2=0
2a(a-4b)-b(a+2b)=?